Hubungan Pengetahuan dengan Kepatuhan Minum Obat Antihipertensi pada Lansia di RSU Bhakti Asih Ciledug - Dianika Supraptiningsih; Ekbert Mandaku; Tanto Tanto; Harun Wahyudi; Reni Afriyani (Pusat Riset dan Inovasi Nasional, 2025)
Background: Hypertension has a high prevalence of 43.11%, which is even higher among the elderly in Indonesia. The treatment of hypertension requires long-term therapy, making medication adherence crucial for controlling blood pressure and preventing complications. Sample: The sample in this study consisted of 76 pregnant women in Tangkil Tengah and Rengas villages. After screening according to inclusion and exclusion criteria, 62 pregnant women were selected as respondents. Method: This study employed a correlational analytical method using a quantitative approach. The sampling technique used was non-probability sampling. The research instrument was a questionnaire that included the variables to be studied. The analysis used was univariate analysis with frequency distribution and percentages, and bivariate analysis using the Statistical Program for Social Science (SPSS). Results: The knowledge of elderly individuals with hypertension about hypertension was categorized as high (9%), moderate (35%), and low (57%), while adherence to antihypertensive medication was categorized as high (24%), moderate (7%), and low (70%). The correlation analysis in this study, using the Chi-square test, showed a significant relationship between the level of knowledge and the level of adherence to antihypertensive medication among the elderly, with a p-value of 0.00. Conclusion: There is a significant relationship between the level of knowledge and the level of adherence to antihypertensive medication among the elderly at RSU Bhakti Asih Ciledug.